HUBUNGAN KEKURANGAN ENERGI KRONIK PADA IBU HAMIL DENGAN KEJADIAN STUNTING DI WILAYAH KERJA PUSKESMAS POOPO - Karni Simbolon, Ceti; Sri Purwanti, Anik (NHM PRESS, 2024)
Background: Chronic energy deficiency (CED) in pregnant women is a significant health problem and has long-term impacts on children's health, including increasing the risk of stunting. Stunting in children is a condition that indicates a chronic lack of nutrition which inhibits a child's physical and cognitive growth. Objective: This study aims to analyze the relationship between chronic energy deficiency in pregnant women and the incidence of stunting in children in the Poopo Health Center working area. Method: This study used a cross-sectional design with a sample of 16 pregnant women selected using purposive sampling. Data was collected through questionnaires and anthropometric measurements of pregnant women as well as measuring the child's height to determine stunting status. Data analysis was carried out using the chi-square test to determine the relationship between CED in pregnant women and the incidence of stunting. Results: Of the 16 samples, 10 pregnant women experienced CED. Of the children born to mothers with CED, 8 of them (80%) experienced stunting. In contrast, of children born to mothers without KEK, only 2 children (20%) experienced stunting. The results of the analysis show that there is a significant relationship between CED in pregnant women and the incidence of stunting in children (p < 0.05). Conclusion: Appropriate nutritional intervention during pregnancy is very important to prevent CED and reduce the risk of stunting in children. Education programs and providing additional nutrition for pregnant women need to be improved to improve the nutritional status of mothers and children in the region.